Thomas Aquinas's earliest treatment of the Divine Essence. Binghamton: Center for Medieval and Renaissance Studies and Institute for Global Cultural Studies. Binghamton University, 1998 - (:unkn) unknown (Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Filosofía Alejandro Korn. Sección de Filosofía Medieval., 1999)
Thomas Aquinas's earliest treatment of the Divine Essence. By E. M. Macierowsky,Binghamton: Center for Medieval and Renaissance Studies and Institute for Global Cultural Studies. Binghamton University, 1998. Reseñado por Julio Castello Dubra.
Fil: Castello Dubra, Julio. Universidad de Buenos Aires; Argentina.
Keywords: FILOSOFÍA MEDIEVAL; DIOS; RESEÑAS BIBLIOGRÁFICAS; EDAD MEDIA; TOMÁS DE AQUINO, SANTO